SOME PHYSICAL LAWS SUCH AS CONSTANT SPEED OF LIGHT CAN BE EXPLAINED ACCORDING TO THE PRINCIPLE THAT ANY MATTER MUST HAVE FINITE ENERGY - Ma, Hua (International Journal of Research -GRANTHAALAYAH, 2022)
In this paper, a physical principle that any matter must have finite energy is first proposed, which is expressed that any matter must have energy and the energy is finite under any conditions. According to this principle and energy conservation principle, some physical laws with unclear reasons are explained: The mass of a composite particle is greater than the sum of the mass of component particles; The potential energy of a composite particle is smaller than the potential energy sum of the component particles; Any massless matter must move at the speed of light under independent conditions; The velocity of static field without mass can be zero; Deriving inverse square law of massless field strength; Conditions for electromagnetic oscillation to form electromagnetic waves.